Biodegradation of diesel oil by Penicillium citrinum UCP 1183 isolated from mangrove sediments (Research, Society and Development, 2022)
Biodegradation is a very effective technology that can be used to recover areas impacted with petroderivatives. In this context, the aim of this work was to investigate the potential of Penicillium sp. (isolated from mangrove sediments in the state of Pernambuco) in the biodegradation of diesel oil. Identification of specie was performed by analyzing the macromorphological and micromorphological structures. The biodegradation study was carried out in Bushnell Haas medium containing the redox indicator 2,6-dichlorophenol indophenol (DCPIP) and the fungus previously acclimated to different concentrations of burnt motor oil. The assay was incubated under static conditions and darkness for 72 h and every 24 h the biodegradation of the petroderivative was verified by UV-Vis spectrophotometry at 600 nm. The characteristics of the fungus indicated that the isolate is Penicillium citrinum. In the acclimation stage, P. citrinum grew in all tested concentrations of burnt motor oil (5, 10, 15 and 20%). In addition, the fungus was able to degrade diesel oil by the proven oxidation-reduction reaction indicated by the change in the color of the indicator from blue (oxidized form) to colorless (reduced form). The spectrophotometric analysis verified the occurrence of the biodegradation of diesel oil, resulting in the maximum value (70%) after 72 h. The present work demonstrates that the mangrove sediment isolate was identified as P. citrinum and it has promising potential for use in diesel oil biodegradation processes in impacted areas.